2016
DOI: 10.1186/s11671-016-1631-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel PVA/MOF Nanofibres: Fabrication, Evaluation and Adsorption of Lead Ions from Aqueous Solution

Abstract: Plain polyvinyl alcohol (PVA) nanofibres and novel polyvinyl alcohol benzene tetracarboxylate nanofibres incorporated with strontium, lanthanum and antimony ((PVA/Sr-TBC), (PVA/La-TBC) and (PVA/Sb-TBC)), respectively, where TBC is benzene 1,2,4,5-tetracarboxylate adsorbents, were fabricated by electrospinning. The as-prepared electrospun nanofibres were characterized by scanning electron microscope (SEM), Fourier transform infrared (FTIR) and thermogravimetric analysis (TGA). Only plain PVA nanofibres followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 37 publications
0
25
0
2
Order By: Relevance
“…The maximum calculated (q e ) value for Pb(II) ions was 171.42 mg/g. Co-MOF [34] have a maximum adsorption capacity corresponding to 50 % of the adsorption capacity value obtained for Cd-H 4 bta while Cu-MOF [35], Fe-MOF [36] and Zr-MOF [37,38] have adsorption capacity corresponding to only 42, 53 and 79 % respectively. The maximum adsorption capacity values of Cd-MOF for Cu(II), Pb(II) and Ni(II) ion (183.43, 171.42 and 120.31 mg/g) respectively indicated that this material is a potential candidate for removing metal ions from aqueous solution.…”
Section: Effect Of Concentration On Percentage Removalmentioning
confidence: 90%
“…The maximum calculated (q e ) value for Pb(II) ions was 171.42 mg/g. Co-MOF [34] have a maximum adsorption capacity corresponding to 50 % of the adsorption capacity value obtained for Cd-H 4 bta while Cu-MOF [35], Fe-MOF [36] and Zr-MOF [37,38] have adsorption capacity corresponding to only 42, 53 and 79 % respectively. The maximum adsorption capacity values of Cd-MOF for Cu(II), Pb(II) and Ni(II) ion (183.43, 171.42 and 120.31 mg/g) respectively indicated that this material is a potential candidate for removing metal ions from aqueous solution.…”
Section: Effect Of Concentration On Percentage Removalmentioning
confidence: 90%
“…Synthesis of Ni-MOF: Ni-MOF was synthesized using the method adopted from Shooto et al [13]. A solvent, DMF of 80 mL was transferred into a round bottom flask.…”
Section: Methodsmentioning
confidence: 99%
“…The pollution of heavy metals in the environment is increasing because of improper disposal of industrial effluents from factories, which manufacture steel, dyes, fertilizers and many others [1]. It is therefore important to remove these pollutants from water.…”
Section: Introductionmentioning
confidence: 99%
“…[105][106][107] Thinfilm nanofiber membranes have been developed for various water treatment processes. For a similar application, Shooto et al [109] reported the fabrication of PVA/La-TBC, PVA/ Sr-TBC, and PVA/La-TBC nanofibers produced by the electrospinning method, where TBC is benzene 1,2,4,5-tetracarboxylate. However, the majority of the applications of nanofiber membranes in water treatment is limited to the microfiltration range, due to the relatively large pore sizes (≈1 µm) of nanofiber structures.…”
Section: Water Treatmentmentioning
confidence: 99%